The Clinical View on Streptococcus anginosus Group – Opportunistic Pathogens Coming Out of Hiding - Pilarczyk-Zurek, Magdalena; Sitkiewicz, Izabela; Koziel, Joanna (Frontiers in Microbiology, 2022)
Three distinct streptococcal species: Streptococcus anginosus, Streptococcus intermedius and Streptococcus constellatus, belonging to the Streptococcus anginosus group (SAG), also known as Streptococcus milleri group, have been attracting clinicians and microbiologists, not only as oral commensals but also as opportunistic pathogens. For years they have been simply classified as so called viridans streptococci, and distinct species were not associated with particular clinical manifestations. Therefore, description of SAG members are clearly underrepresented in the literature, compared to other medically relevant streptococci. However, the increasing number of reports of life-threatening infections caused by SAG indicates their emerging pathogenicity. The improved clinical data generated with the application of modern molecular diagnostic techniques allow for precise identification of individual species belonging to SAG. This review summarizes clinical reports on SAG infections and systematizes data on the occurrence of individual species at the site of infection. We also discuss the issue of proper microbiological diagnostics, which is crucial for further clinical treatment.